The oregon and santa fe trails - Smith, Jennie Ruth (My University, 1894)
Introduction: Since the creation man’s onward movement has been westward. He has watched the orb of day rise, run its magnificent course across the heavens, and sink in all its gold and purple glory in the west. It seems natural for humanity to follow a brilliant leader, and so man has girded himself and commenced his long race after the sun. He set out from the Highlands of Central Asia with his face turned toward Europe. He bridged the Hellespont and built up historic Greece whose crystal atmosphere, perfect skies, fairy vales and landscapes of wondrous beauty united to inspire in her subjects, the spirit of artist, poet, or sculptor. Soon he reached Italy, and imperial Rome “who sat on her seven hills and from her throne of beauty ruled the world,” sprang into her power as if by magic under his hand. Further to the worth a multitude came surging westward, with the Celts as vanguard followed by the Tentous, who were in turn jostled and crowded onward by the advancing Sclaves. From these all the great nations of Europe were formed. Nor is this the extent of the influence of a westward impulse,
Citation: Smith, Jennie Ruth. The oregon and santa fe trails. Senior thesis, Kansas State Agricultural College, 1894.
Morse Department of Special Collections
Keywords: Migration; Sante Fe Trail; Oregon trail; Trails; History; Anthropology; Theses; Manuscripts (documents)